1990
DOI: 10.1182/blood.v76.11.2229.bloodjournal76112229
|View full text |Cite
|
Sign up to set email alerts
|

Species specificity of human interleukin-3 demonstrated by cloning and expression of the homologous rhesus monkey (Macaca mulatta) gene

Abstract: To enable preclinical studies on homologous interleukin-3 (IL-3) in primate species, we isolated the gene encoding Rhesus monkey IL-3 (RhIL- 3). The nucleotide sequence of the RhIL-3 gene displayed 92.9% homology with that of the human IL-3 (hIL-3) gene. The isolated RhIL-3 gene encodes a 143-amino acid (aa) precursor polypeptide, nine C-terminal residues shorter than the human protein. Protein homology was found to be 89.5% for the signal peptide (19 aa) and 80.5% for the mature protein (124 aa). Comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…To optimize engraftment rates, supplementation with human cytokines seems to be beneficial [10, 11]. While several hematopoietic active cytokines are cross‐reactive between mice and humans and can provide human hematopoietic cells with growth factors, interleukin‐3 (IL‐3), formerly known as multi‐colony‐stimulating factor, is highly species specific [12]. The support of early human hematopoiesis in the chimeric bone marrow with IL‐3 is probably crucial for human cell engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…To optimize engraftment rates, supplementation with human cytokines seems to be beneficial [10, 11]. While several hematopoietic active cytokines are cross‐reactive between mice and humans and can provide human hematopoietic cells with growth factors, interleukin‐3 (IL‐3), formerly known as multi‐colony‐stimulating factor, is highly species specific [12]. The support of early human hematopoiesis in the chimeric bone marrow with IL‐3 is probably crucial for human cell engraftment.…”
Section: Introductionmentioning
confidence: 99%
“…They can be bred in captivity, and they are not endangered, although the surge in vaccine research for HIV and bioterrorism agents has produced a worldwide shortage of captive pathogen-free animals. Macaque and baboon hematopoietic cells (HSCs) respond to all human hematopoietic cytokines, with similar concentrations required for maximal in vitro stimulation, with the exception of human interleukin 3 (IL-3), which must be added to macaque cells at a 10-fold higher concentration to yield the same degree of colony formation as in baboons (Burger et al, 1990).…”
Section: Commentary Nonhuman Primate Modelsmentioning
confidence: 99%
“…A comparison of 16 asthmatics to 12 healthy controls identified that miRNA (miR)-221 was discovered to be increased (17). The study of Burger et al (18) revealed that decreased airway inflammation may be triggered by blocking miR-221 in a mouse asthma model induced by ovalbumin, demonstrating the function of miR-221 in asthma. T cells have been the focus in the majority of investigations on miRNAs in the blood for asthma risk.…”
Section: Introductionmentioning
confidence: 99%